Profil Kemampuan Berpikir Kritis Siswa Materi Getaran Dengan Model Learning Cycle 5E - Nor Hayat; Luvia Ranggi Nastiti; Hadma Yuliani (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
The purpose of this study was to describe the profile of students' critical thinking skills on vibration material with the implementation of the Learning Cycle 5E model. Quantitative research method quasi-experimental single-group pretest-posttest design. The study included 30 students from class VIII-3 SMP Negeri 1 Palangka Raya in the academic year 2024/2025 who were selected using purposive sampling technique. The measurement instrument was an essay test consisting of eight question items constructed based on the dimensions of critical thinking skills. The results of data analysis revealed that the mean score of the baseline pretest measurement of students' critical thinking skills reached 34 which then experienced enhancement to 59.43 in the endpoint posttest measurement. Computation of normalized gain score resulted in a mean value of 0.372 which is categorized as improvement with moderate magnitude. The conclusion on the research results shows that the implementation of the Learning Cycle 5E model has a positive impact on the cultivation of students' critical thinking skills, especially in the context of vibration material in science learning. For further research, the implementation of the Learning Cycle 5E model is carried out on different materials with more samples, and integrates qualitative analysis to understand the cognitive mechanisms involved in the process of improving students' critical thinking skills.